Digital games adopted by adults—A documental approach through meta-analysis - Pinheiro, A.; Oliveira, A.; Alturas, B.; Cruz, M. (Information, 2024)
The gaming industry has seen a considerable expansion thanks to the ever-increasing and widespread consumption of digital games in diﬀerent contexts of use and across all age groups. We are witnessing a commercial boom and awakening the attention of researchers from diﬀerent scientiﬁc areas to address an interdisciplinary topic. Digital games consumption has inspired some studies investigating the use and adoption of these games and, in this context, we ask: “how has the use and adoption of digital games by adults been studied?”. We conducted a documental study with a meta-analysis approach to answer these questions, considering the most relevant research papers published in the last ﬁfteen years, according to a set of inclusion criteria. The planned objectives consider identifying the main dimensions in the studies about the use and adoption of digital games by adults and the ﬁndings of this study delineate several dimensions as prospective latent variables for inclusion in future studies within acceptance models for digital games. Furthermore, our research illuminates the socialization dimension, particularly when amalgamated with other conceptual dimensions. This nuanced understanding underscores the intricate interplay between various factors inﬂuencing the acceptance and adoption of digital gaming technologies.